Christianity in Northern Ghana: Missionary Impact - Paul Kang-Ewala Diboro (E-Journal of Religious and Theological Studies, 2020)
The impact of Christianity in Northern Ghana regarding the subject of development and the promotion of human lives have not been duly recognized. This article brings to light the contributions of some missionary groups in Northern Ghana who for some years pioneered the developmental cause in the Northern corridors of Ghana. Assessing some of the developmental projects and initiatives undertaken by these Churches as an aspect of their mission, this article demonstrates how the missionary activities in Ghana, especially in the North, have laid the foundations for the developmental agenda of the Christian faith in Ghana. The article contends that, if not for the Church (Christianity) in the North, the area would have lagged in terms of education, health and other important socioeconomic developments that promotes the holistic development of a people. Methodologically, the historical approach is employed, and the data used for this article is gleaned from relevant literature on indigenous Northern Christian missions.